6(-1+2c)=5(2+2c)

Simple and best practice solution for 6(-1+2c)=5(2+2c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-1+2c)=5(2+2c) equation:


Simplifying
6(-1 + 2c) = 5(2 + 2c)
(-1 * 6 + 2c * 6) = 5(2 + 2c)
(-6 + 12c) = 5(2 + 2c)
-6 + 12c = (2 * 5 + 2c * 5)
-6 + 12c = (10 + 10c)

Solving
-6 + 12c = 10 + 10c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-10c' to each side of the equation.
-6 + 12c + -10c = 10 + 10c + -10c

Combine like terms: 12c + -10c = 2c
-6 + 2c = 10 + 10c + -10c

Combine like terms: 10c + -10c = 0
-6 + 2c = 10 + 0
-6 + 2c = 10

Add '6' to each side of the equation.
-6 + 6 + 2c = 10 + 6

Combine like terms: -6 + 6 = 0
0 + 2c = 10 + 6
2c = 10 + 6

Combine like terms: 10 + 6 = 16
2c = 16

Divide each side by '2'.
c = 8

Simplifying
c = 8

See similar equations:

| (9x-7)+4=6 | | 14-18=m | | y=7n-12 | | 4x+2=9x+2 | | 17-9x=18+7x | | 8-9x=18+7x | | -8-9x=18+7x | | 3y-6x=33 | | -235-8m=75 | | 5x+1y=300 | | 0.5(3x+10)(6x)=816 | | 25v+150=225 | | 2.3t=87 | | 3x+8+4x-5= | | x+45=105 | | m+14-18=m | | 5x^2+10x=-4 | | -40x^3y^2-64x^3y+16x^2y= | | 14.2=50.2-y | | 7r+8=37r+14 | | 4x^2-54x+108=0 | | .666w=58 | | 2(10+x)=38 | | 8h+3k-3(6h-3k)= | | 22+y=31 | | -8-5x=14+3x | | 2(a+1)=-5.6 | | 18y^3+60y^2+50y=0 | | 5n-2=55 | | 3x+y=345 | | 10x-6x-37=71 | | 121=6x-1 |

Equations solver categories